PERENCANAAN PAJAK, ASET PAJAK TANGGUHAN, BEBAN PAJAK TANGGUHAN, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Anggelina Wati (Jurnal Kajian Akuntansi dan Auditing, 2023)
This study aims to determine the effect of tax planning, deferred tax assets, deferred tax expense, leverage, and company size on profit management in manufacturing companies listed on the Indonesia Stock Exchange. This research is a quantitative research that uses secondary data. The population in this study is all manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period obtained from www.idx.co.id. The research sample was selected using the purposive sampling method, so that the sample obtained was as many as 69 companies. Hypothesis testing was performed by multiple linear regression analysis using SPSS version 26. The results showed that the independent variables, namely tax planning, deferred tax assets, deferred tax burden, leverage, and company size, were in front of the dependent variable, namely profit management.